Study of reading habits 1990 - Katrineholm and Eskilstuna - Weibull, Lennart (University of Gothenburg, 1993)
This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of two municipalities in Södermanland: Katrineholm and Eskilstuna. The number of questions put in this survey is considerable smaller than in previous surveys. Unlike the other readership studies this survey was carried through with telephone interviews.

This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of two municipalities in Södermanland: Katrineholm and Eskilstuna. The number of questions put in this survey is considerable smaller than in previous surveys. Unlike the other readership studies this survey was carried through with telephone interviews.
Läsvanestudien 1990 - Katrineholm och Eskilstuna
Keywords: internal politics; inrikespolitik; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap